2018
DOI: 10.1371/journal.pone.0203637
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled pilot study of the effects of vitamin D supplementation on balance in Parkinson's disease: Does age matter?

Abstract: ObjectivesTo explore if short term, high dose vitamin D supplementation is safe and improves balance in persons with Parkinson's disease (PD).MethodsA pilot randomized, double-blind intervention trial to measure the effects of 16 weeks of high dose vitamin D (10,000 IU/day) on balance as well as other motor and non-motor features of PD. We measured balance, gait, strength, falls, cognition, mood, PD severity, and quality of life before and after 16 weeks of high dose vitamin D supplementation or placebo. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 41 publications
(42 reference statements)
0
44
0
1
Order By: Relevance
“…The most important studies on vitamin D supplementation in PD patients are shown in Table 2. An interventional trial supported the role of vitamin D in postural balance of PD patients and suggested that daily supplementation of vitamin D could improve the balance of younger PD patients [148]. Other studies have also confirmed that supplemental 25(OH)D has beneficial effects on strength and balance in older adults [149].…”
Section: Vitamin D Supplementation In Pd Patientsmentioning
confidence: 94%
See 1 more Smart Citation
“…The most important studies on vitamin D supplementation in PD patients are shown in Table 2. An interventional trial supported the role of vitamin D in postural balance of PD patients and suggested that daily supplementation of vitamin D could improve the balance of younger PD patients [148]. Other studies have also confirmed that supplemental 25(OH)D has beneficial effects on strength and balance in older adults [149].…”
Section: Vitamin D Supplementation In Pd Patientsmentioning
confidence: 94%
“…However, the complex automatic postural response not only requires muscle function, but also involves the spinal cord, midbrain/brainstem, and cerebellum/basal ganglia/cerebral cortex [150,151]. In addition, vitamin D 3 supplementation has an age-dependent effect on PD [148]. Another randomized controlled trial of vitamin D supplementation found that vitamin D 3 supplementation may retard the progression of PD for a short period in patients with FokI CT and TT genotypes [41].…”
Section: Vitamin D Supplementation In Pd Patientsmentioning
confidence: 99%
“…In line with this, a double-blind, placebo-controlled intervention study from Suzuki and colleagues, including 114 PD patients, was able to reveal that supplementation of 1200 IU vitamin D 3 /day prevents disease progression in a VDR FokI genotype-dependent manner [87]. Moreover, high-dose supplementation of vitamin D (10,000 IU/day) resulted in significant improved balance measured via sensory organization test in PD patients with an age of 52-66 but not in older individuals [88].…”
Section: Parkinson's Diseasementioning
confidence: 98%
“…10 The Endocrine Society Clinical Practice Guideline defines Vitamin D deficiency as 25(OH)D level <20 ng/mL and insufficiency as 21 to 29 ng/mL. 11 Some studies have linked deficient 25(OH) vitamin D to neuropsychological diseases such as sleep disorders [12][13][14] , which showed that 25…”
Section: (Oh) Vitamin D Is Essential For Good Bone Health and Deficmentioning
confidence: 99%